Sphingomonas sp. Cra20 Increases Plant Growth Rate and Alters Rhizosphere Microbial Community Structure of Arabidopsis thaliana Under Drought Stress - Luo, Yang; Wang, Fang; Huang, Yaolong; Zhou, Meng; Gao, Jiangli; Yan, Taozhe; Sheng, Hongmei; An, Lizhe (Frontiers in Microbiology, 2019)
The rhizosphere is colonized by a mass of microbes, including bacteria capable of promoting plant growth that carry out complex interactions. Here, by using a sterile experimental system, we demonstrate that Sphingomonas sp. Cra20 promotes the growth of Arabidopsis thaliana by driving developmental plasticity in the roots, thus stimulating the growth of lateral roots and root hairs. By investigating the growth dynamics of A. thaliana in soil with different water-content, we demonstrate that Cra20 increases the growth rate of plants, but does not change the time of reproductive transition under well-water condition. The results further show that the application of Cra20 changes the rhizosphere indigenous bacterial community, which may be due to the change in root structure. Our findings give new insights into the complex mechanisms of plant and bacterial interactions. The ability to promote the growth of plants under water-deficit can contribute to the development of sustainable agriculture.